Contextual Challenges in Police-Assisted Substance Use Referral Programs: Impact of Covid-19 and Black Lives Matter Movement. Issue 1 (December 2022) - Liu, Jessica; Heckel, Emily; Coroiu, Adina; Rees, Vaughan W.
Background : Police assisted referral (PAR) programs provide people with substance use disorders (SUD) with a non-arrest treatment pathway, yet systemic barriers, including stigma and access to treatment services, may limit engagement. We sought to understand how the dual contextual challenges of COVID-19 and the Black Lives Matter movement have impacted PAR programs. Methods: Participants completed semi-structured interviews between July and September 2020. Transcribed interviews were analyzed qualitatively to extract emergent codes and themes. Results: Key themes included: adoption and reach of adapted remote services, and barriers to access; and questions on the role of police as health service providers, including police embeddedness in the community. COVID-related social distancing demands undermined police engagement with people with SUD. Treatment providers and advocates reported moderate success in utilizing remote interventions as workarounds. While participants acknowledged the Black Lives Matter movement's criticism of police, many saw continued value in police involvement in substance use interventions, due to their accessibility in communities and capacity for rapid response. Conclusions: PAR programs quickly adapted to a largely remote format, increasing longer-term accessibility. While Black Lives Matter had little direct impact on PAR programs, concerns about police-community relations were acknowledged. Recommendations include further police training to enhance trust and reduce stigma, and wider integration of digitally-based substance use referral options.